Report of the Health Section of the World Federation of Education Associations. - American Child Health Association; Metropolitan Life Insurance Company; World Federation of Education Associations Health Section (New York, N.Y. American Child Health Association and the Metropolitan Life Insurance Co., 1926)
Biennial
Description based on: July 21-24, 1925.
Vol. for 1929 issued without title.
Keywords: School hygiene -- Congresses; Health education -- Periodicals